Emerging role of exosomes in vascular diseases - Ren, Yi; Zhang, Honggang (Frontiers in Cardiovascular Medicine, 2023)
Exosomes are small vesicles wrapped in a lipid membrane bilayer that are secreted by most cells in the body. Their contents include nucleic acids, proteins, and lipids. Exosomes can transmit material molecules between cells and consequently have a variety of biological functions, participating in disease development while having potential value as biomarkers and therapeutics. There is growing evidence that exosomes are vital mediators of vascular remodelling. Endothelial cells (ECs), smooth muscle cells (SMCs), inflammatory cells, and adventitial fibroblasts (AFs) can communicate through exosomes, which are associated with inflammatory responses, cell migration and proliferation, and cell metabolism, leading to changes in vascular function and structure. Essential hypertension (EH), atherosclerosis (AS), and pulmonary arterial hypertension (PAH) are the most common vascular diseases and are associated with significant vascular remodelling. This paper reviews the latest research progress on the involvement of exosomes in vascular remodelling through intercellular information exchange and provides new ideas for understanding related diseases.